Acute and chronic total occlusion of the left circumflex artery following unprotected left main stenting: two contrasting cases. Issue 6 (September 2015) - Watanabe, Yusuke; Takagi, Kensuke; Nakamura, Sunao
Abstract : Supplemental Digital Content is available in the text.